2016
DOI: 10.4236/eng.2016.810061
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Baked Clay Bricks Fired with Alternate Fuels

Abstract: Coal is used as a traditional fuel for firing of clay bricks in kilns. The cost of coal is high and is increasing continuously. This paper describes the effect of alternate fuels on compressive strength, water absorption and density of fired clay bricks. The alternate fuels used in this study were 1) rapeseed husk (Type I), 2) combination of sugarcane-bagasse, rice husk and used clothes (Type II) and 3) coal (Type III). The results show that compressive strength of bricks fired using Type I and Type II fuels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…4b revealed that the ASSJ sample had the lowest percentage of water absorption summation of about 43.5 % compared to the other samples. This validates the description of its plasticity index at 19 % as "medium plasticity" due to the addition of AJA as an addictive to ASH sample which improved the drying strength of the AASJ clay with reduced problem of fabrication, drying and shrinkage of the manufactured brick [25,32 ] For the raw state of the burnt bricks, an increase in bulk density was noticed from 1. 03 / 3 to 1.…”
Section: Element Composition Analysis From Xrfsupporting
confidence: 75%
“…4b revealed that the ASSJ sample had the lowest percentage of water absorption summation of about 43.5 % compared to the other samples. This validates the description of its plasticity index at 19 % as "medium plasticity" due to the addition of AJA as an addictive to ASH sample which improved the drying strength of the AASJ clay with reduced problem of fabrication, drying and shrinkage of the manufactured brick [25,32 ] For the raw state of the burnt bricks, an increase in bulk density was noticed from 1. 03 / 3 to 1.…”
Section: Element Composition Analysis From Xrfsupporting
confidence: 75%
“…The retention at the maximum firing temperature is also an important parameter considering the structural characteristics of the final product. A more extended retention period has evidently a positive influence on the final properties of the product [25].…”
Section: Introductionmentioning
confidence: 99%
“…Many kilns also use a mixture of fuels. Although, some authors describe coal as the traditional fuel in brick firing [84,85]. In other cases, fuels are added separately and in others, they are pre-mixed.…”
Section: Fuel Used In Bkmentioning
confidence: 99%